fig-2 - 50 projects in 50 Weeks - Üstek, Fatoş; Buck, Louisa; Douglas, Caroline; Obrist, Hans Ulrich 1968-; Williams, Gilda; Wood, Catherine 1973- (Black Dog Publishing, 2017)
Fig-2' brings together material from the eponymous arts programme staged at ICA Studio in 2015. A revival of Mark Francis and Jay Jopling's Fig-1 project that took place in 2000, Fig-2 staged 50 week-long residencies with contemporary artists. In every case, the artists were only announced the week before their residency began. Work that emerged from each of the 50 exhibitions is presented in this publication, as well as a series of artist interviews, curatorial texts and images of the work or performance in situ. Artists whose work are featured include Eva Rothschild and Suzanne Treister, while commentators include Catherine Wood (Curator of Performance at the Tate Modern) and Hans-Ulrich Obrist (Co-Director of The Serpentine Gallery)
Keywords: Arts, Modern / 21st century / Exhibitions; Ausstellungskatalog -- ICA Studio - The Mall -- 05.01.2015-20.12.2015 -- London